El principio de concurrencia en los procedimientos de Ínfima Cuantía y su impacto en las contrataciones estatales emergentes. - Amán Cauja, Jeniffer Alejandra (2023)
This academic work develops an analysis regarding the principle of concurrence in public procurement processes under the modality of Small Value Procurement (Ínfima Cuantía) and its incidence in emerging state purchases. For this purpose, a doctrinal, legal, and critical study is used on the model of contracting for Small Value Procurement, linked to the historicity of public purchases within the country and its evolution over the years. At all times, the principle of concurrence is conjugated as a basis for understanding the subject matter. In favor of determining compliance with concurrence in emerging state purchases subject to a Small Value Procurement. Undeniably, El Servicio Nacional de Contratación Pública, through the incorporation of technological tools such as Small Value Procurement Needs, limits compliance with the principle of concurrence since the technological gap in the management of platforms leads to the non-observance of the legal nature of Small Value Procurement as indicated by the regulations governing the Ecuadorian State, preventing the promotion of micro productive units.